1998
DOI: 10.1111/j.1540-8159.1998.tb01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radiofrequency Catheter Ablation on Parasympathetic Denervation: A Comparison of Three Different Ablation Sites

Abstract: These data suggest that RF ablation produces parasympathetic denervation at all three sites along the mitral or tricuspid annulus and that parasympathetic fibers may be located predominantly in the septal area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 16 publications
0
23
1
4
Order By: Relevance
“…In our results, the magnitude of the vagal damage caused by the RPV RFCA was greater than that by the PS RFCA mimicking AVNRT ablation in which the occurrence of inappropriate sinus node tachycardia has been reported. [6][7][8][9][10][11][12] This result was reasonable because the RPV is closer anatomically to the RPVAFP than to the PS area, and therefore it is possible that a more proximal part of the vagal network bundle is distributed to the right atrium, part of which may innervate the SA node. Kocovic, et al 7) and Madrid, et al 8) clinically observed that RFCA of a left-sided accessory pathway produced little or no vagal Figure 7.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In our results, the magnitude of the vagal damage caused by the RPV RFCA was greater than that by the PS RFCA mimicking AVNRT ablation in which the occurrence of inappropriate sinus node tachycardia has been reported. [6][7][8][9][10][11][12] This result was reasonable because the RPV is closer anatomically to the RPVAFP than to the PS area, and therefore it is possible that a more proximal part of the vagal network bundle is distributed to the right atrium, part of which may innervate the SA node. Kocovic, et al 7) and Madrid, et al 8) clinically observed that RFCA of a left-sided accessory pathway produced little or no vagal Figure 7.…”
Section: Discussionmentioning
confidence: 87%
“…[6][7][8][9][10][11][12] Kocovic, et al 7) first described the parasympathetic damage that occurs in combination with an atrial septal RFCA during therapy for atrioventricular (AV) nodal reentrant tachycardia (AVNRT) or AV reciprocating tachycardia utilizing a septal Kent bundle, and speculated that it was due to injury to the vagal ganglia or neural fibers existing in that area. They also reported that RFCA of a left lateral Kent bundle did not cause any parasympathetic damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Since their study, it has been observed that heart rate increases and heart rate variability decreases after the ablation of the fast atrioventricular nodal pathway, 8,9,12 slow atrioventricular nodal pathway, 9,12,14,16,19,28 left free wall accessory pathway, 14 right free wall accessory pathway, 16 and the attenuation of vagal indices of heart rate variability. These investigators have speculated that autonomic dysfunction might play an important role in its mechanism.…”
Section: Effect Of Radiofrequency Ablation On Heart Rate Variabilitymentioning
confidence: 99%
“…Recently, heart rate variability has been used widely to reflect the autonomic nervous system (sympathetic and parasympathetic) activity on the sinus node. [8][9][10][11][12][13][14][15][16][19][20][21] Therefore, the purpose of the present study was to evaluate the effects of linear ablation of the cavotricuspid isthmus on the autonomic nervous function of the sinus node using heart rate variability analysis, and to investigate the distribution of efferent autonomic nervous fibers in the human heart.…”
mentioning
confidence: 99%